2019
DOI: 10.1016/j.kint.2018.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density, bone turnover markers, and incident fractures in de novo kidney transplant recipients

Abstract: Kidney transplant recipients are at increased risk of fractures. This prospective observational study investigated whether areal bone mineral density (aBMD) as assessed by dual-energy x-ray absorptiometry can predict incident fragility fractures in de novo kidney transplant recipients and whether bone turnover markers increase diagnostic accuracy. Parameters of bone mineral metabolism including parathyroid hormone (PTH), fibroblast growth factor 23, sclerostin, calcidiol and calcitriol, and bone turnover marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 59 publications
4
66
0
2
Order By: Relevance
“…To date, only one retrospective study, total hip DXA measurement after KT was associated with increased fracture risk. In addition, a recent prospective study had similar findings [81,82]. Despite the insufficient evidence for KTRs, Vitamin D Deficiency in Renal Disease DOI: http://dx.doi.org /10.5772/intechopen.88928 KDIGO suggests the use of BMD testing in all stages of post-transplant CKD in KTRs with high risk for osteoporosis, if the measurement will have effect on treatment.…”
Section: Ptmbd: Bone Diseasementioning
confidence: 89%
“…To date, only one retrospective study, total hip DXA measurement after KT was associated with increased fracture risk. In addition, a recent prospective study had similar findings [81,82]. Despite the insufficient evidence for KTRs, Vitamin D Deficiency in Renal Disease DOI: http://dx.doi.org /10.5772/intechopen.88928 KDIGO suggests the use of BMD testing in all stages of post-transplant CKD in KTRs with high risk for osteoporosis, if the measurement will have effect on treatment.…”
Section: Ptmbd: Bone Diseasementioning
confidence: 89%
“…Our present results showed that (i) respectively, 34.5% and 6.1% of the patients presented osteopenia and osteoporosis one month after kidney transplantation and (ii) 1% of the patients presented a fracture in the 24 months following kidney transplantation. Evenepoel et al have shown that over a median follow-up period of 5.2 years, 38 out of 518 (7.3%) de novo renal transplant recipients experienced a fragility fracture; this corresponds to an incidence rate of 14.2 fractures per 1000 person-years [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 To confirm these data in humans, we performed a post hoc analysis on data collected in the frame of prospective, observational studies in patients referred for kidney transplantation. 3 Patients receiving cinacalcet (cases, n ¼ 65) were randomly matched 3:1 on PTH levels to patients free of cinacalcet (controls, n ¼ 166). PTH, calcium, and phosphate levels were comparable, whereas bone-specific alkaline phosphatase, intact procollagen type I N-terminal propeptide, and tartrate-resistant acid phosphatase type 5b were significantly higher in cases versus controls (Figure 1).…”
Section: Clinical Evidence Of Direct Bone Effects Of Cinacalcetmentioning
confidence: 99%
“…Previous studies have also reported that nonadherence was associated with both DSA and graft survival. 2,3 Then, it is unclear whether it is nonadherence that leads to the development of DSA and TCMR, which then resulted in worse transplant outcomes.…”
Section: Clinical Evidence Of Direct Bone Effects Of Cinacalcetmentioning
confidence: 99%
See 1 more Smart Citation